Limited 12-hour pharmacokinetic assessment of CBD and CBDA isolates compared to their full-spectrum extracts in healthy adult beagles - Wang, Tongxin Charlotte; Wakshlag, Joseph J.; Lyubimov, Alex; Zakharov, Alexander; Gomez, Beatriz; Schwark, Wayne; Trottier, Nathalie L. (Frontiers in Veterinary Science, 2025)
IntroductionThe rapidly expanding market for therapeutic cannabinoid products has intensified research on their safety and efficacy in pets. Full-spectrum hemp extracts contain compounds such as terpenoids and flavonoids that may act synergistically via the “entourage effect,” yet their application in companion animals remains underexplored. This study assessed the pharmacokinetics and safety of isolated and full-spectrum cannabinoids in dogs.MethodsEight healthy adult Beagle dogs (four males and four females) were randomly assigned to a 4 × 4 Latin square design (two dogs per kennel, same sex), consisting of four experimental periods and four treatments: CBD isolate (1 mg/kg), CBDA isolate (1 mg/kg), CBDA full spectrum (FS) (1 mg/kg), and a combined CBD/CBDA FS (1 mg/kg). Treatments were administered twice daily (every 12 h). In the morning, dogs received their assigned treatment following their daily ration of dry kibble and were immediately offered 122 grams of wet food. Each experimental period lasted 1 week and was followed by a three-week washout period.ResultsNo adverse events were associated with any treatment. CBDA showed higher Cmax and AUC than CBD in both isolate and FS forms (p < 0.001). CBDA in CBD/CBDA FS had a shorter Tmax compared to CBD (p = 0.019). Mean residence time and elimination half-life did not differ among treatments.ConclusionCBDA demonstrated superior absorption compared to CBD. No evidence supported enhanced absorption from full-spectrum products, suggesting the “entourage effect” may involve receptor-level interactions rather than absorption. All treatments were well tolerated, with normal CBC and chemistry results, indicating that administering CBD or CBDA, either as isolates or in full-spectrum extracts, at 1 mg/kg every 12 h for 1 week is safe in healthy adult dogs. This is the first comprehensive comparison of full-spectrum, isolate, and acidic cannabinoid forms in dogs.